Ayurvedic Management of Atopic Dermatitis – A Case Report - Aneesh, M S (International Research Journal of Ayurveda & Yoga, 2024)
Background: Children’s eczema, often called atopic dermatitis, starts before age 5 and lasts a lifetime. From dry, itchy skin to painful rashes, it disrupts sleep and daily life. Vicharchika, a skin condition similar to Ayurveda, connects with atopic dermatitis based on its causes, symptoms, and overall presentation. Materials and Methods: A boy, aged 4 years old, complained of skin lesions over bilateral lower limbs associated with roughness, scaling, and severe itching all over the body for 6 months. The case was diagnosed as Vicharchika (an Ayurvedic diagnosis for atopic dermatitis). Ayurvedic remedies were used to treat the patient for 2 months. Clinical symptoms and ImageJ software analysis of photographs of the lesions assessed the disease severity. Results: The treatments given were successful in reducing the symptoms. This case study demonstrates the efficacy of Ayurvedic treatment for atopic dermatitis. Conclusions: The study concluded that Ayurvedic therapy was significantly effective in treating atopic dermatitis.